2017
DOI: 10.1371/journal.pone.0181453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous glucagon-like peptide-2 and distal bowel resection on intestinal and systemic adaptive responses in rats

Abstract: ObjectiveTo determine the effects of exogenous glucagon-like peptide-2 (GLP-2), with or without massive distal bowel resection, on adaptation of jejunal mucosa, enteric neurons, gut hormones and tissue reserves in rats.BackgroundGLP-2 is a gut hormone known to be trophic for small bowel mucosa, and to mimic intestinal adaptation in short bowel syndrome (SBS). However, the effects of exogenous GLP-2 and SBS on enteric neurons are unclear.MethodsSprague Dawley rats were randomized to four treatments: Transected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Likewise, in studies with different animal models, the intraperitoneal administration of GLP-2 also showed contradictory results. Thus, the GLP-2R expression was downregulated in the ileum of 21-day-old sows [ 41 ], in the mucosal of TPN-mice [ 39 ], and in the jejunum of rats with short bowel syndrome, but not in rats with a distal bowel resection [ 42 ]. Likewise, the GLP-2R expression was reduced in both the anastomotic segments and in the ileal samples recovered after ileal resection and isolated laparotomy of rats after teduglutide administration [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in studies with different animal models, the intraperitoneal administration of GLP-2 also showed contradictory results. Thus, the GLP-2R expression was downregulated in the ileum of 21-day-old sows [ 41 ], in the mucosal of TPN-mice [ 39 ], and in the jejunum of rats with short bowel syndrome, but not in rats with a distal bowel resection [ 42 ]. Likewise, the GLP-2R expression was reduced in both the anastomotic segments and in the ileal samples recovered after ileal resection and isolated laparotomy of rats after teduglutide administration [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the trophic effects on the small intestinal mucosa by GLP-2 stimulation are well described [40][41][42][43], the functional relevance of small bowel villus growth is less clear. The mechanistic implication of villus growth is called into question by translational observations: 1) Villus growth in response to Teduglutide is not in the same order of magnitude as a reduction of parenteral support (PS) [13], and enterocyte mass expansion does not correlate with PS reduction [42].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that rats who underwent SBR showed an increased proportion of myenteric nitrergic neurons that correlated with a thicker muscularis propria and higher crypt cell proliferation in both the jejunum and colon. 117 This study suggested that modulation of the neuronal population potentially could be a compensatory mechanism that reduces motility and improves nutrient/fluid absorption. 117 …”
Section: Impact Of Microbiota On Shaping the Enteric Nervous System Dmentioning
confidence: 90%
“… 117 This study suggested that modulation of the neuronal population potentially could be a compensatory mechanism that reduces motility and improves nutrient/fluid absorption. 117 …”
Section: Impact Of Microbiota On Shaping the Enteric Nervous System Dmentioning
confidence: 90%